Impact of molecular imaging on the diagnostic process in a memory clinic. Issue 4 (19th November 2012) - Ossenkoppele, Rik; Prins, Niels D.; Pijnenburg, Yolande A.L.; Lemstra, Afina W.; van der Flier, Wiesje M.; Adriaanse, Sofie F.; Windhorst, Albert D.; Handels, Ron L.H.; Wolfs, Claire A.G.; Aalten, Pauline; Verhey, Frans R.J.; Verbeek, Marcel M.; et al.
Abstract: Background: [ 11 C]Pittsburgh compound B ([ 11 C]PIB) and [ 18 F]‐2‐fluoro‐2‐deoxy‐D‐glucose ([ 18 F]FDG) PET measure fibrillar amyloid‐β load and glucose metabolism, respectively. We evaluated the impact of these tracers on the diagnostic process in a memory clinic population. Methods: One hundred fifty‐four patients underwent paired dynamic [ 11 C]PIB and static [ 18 F]FDG PET scans shortly after completing a standard dementia screening. Two‐year clinical follow‐up data were available for 39 patients. Parametric PET images were assessed visually and results were reported to the neurologists responsible for the initial diagnosis. Outcome measures were (change in) clinical diagnosis and confidence in that diagnosis before and after disclosing PET results. Results: [ 11 C]PIB scans were positive in 40 of 66 (61%) patients with a clinical diagnosis of Alzheimer's disease (AD), 5 of 18 (28%) patients with frontotemporal dementia (FTD), 4 of 5 (80%) patients with Lewy body dementia, and 3 of 10 (30%) patients with other dementias. [ 18 F]FDG uptake patterns matched the clinical diagnosis in 38 of 66 (58%) of AD patients, and in 6 of 18 (33%) FTD patients. PET results led to a change in diagnosis in 35 (23%) patients. This only occurred when prior diagnostic certainty was <90%. Diagnostic confidence increased from 71 ± 17% before to 87 ± 16% after PET ( p < .001). Two‐year clinical follow‐up ( n = 39) showed that [ 11 C]PIB and [ 18 F]FDG predicted progression to AD for patients with mild cognitive impairment, and that the diagnosis of dementia established after PET remained unchanged in 96% of patients. Conclusions: In a memory clinic setting, combined [ 11 C]PIB and [ 18 F]FDG PET are of additional value on top of the standard diagnostic work‐up, especially when prior diagnostic confidence is low.